1998
DOI: 10.1159/000010039
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, Hemoglobin Concentration and Pregnancy-Induced Hypertension

Abstract: The aim of the study was to assess the effect of cigarette smoking on first- to second-trimester change in hemoglobin (Hb) concentration and the presence of pregnancy-induced hypertension (PIH). In smokers and non-smokers the mean difference between the first- and second-trimester Hb concentration was 1.5–1.6 and 1.3 g/dl, respectively (p < 0.0001). The incidence of PIH among smokers and non-smokers was 4.0 and 7.5%, respectively (p < 0.0001). The risk of PIH increased with increasing second-trimester Hb. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…25 Our database holds information on maternal smoking, which is a strong and common risk factor for fetal growth restriction and seems to be negatively associated with PIH. 26 As expected, adjustment for smoking increased the association of SGA with later PIH (data not shown). The Medical Birth Registry also holds data on conditions like chronic renal disease, chronic hearth disease, rheumatoid arthritis, diabetes mellitus type 1 and 2, and gestational diabetes.…”
Section: Rasmussen and Irgens Pregnancy-induced Hypertension In Womensupporting
confidence: 71%
“…25 Our database holds information on maternal smoking, which is a strong and common risk factor for fetal growth restriction and seems to be negatively associated with PIH. 26 As expected, adjustment for smoking increased the association of SGA with later PIH (data not shown). The Medical Birth Registry also holds data on conditions like chronic renal disease, chronic hearth disease, rheumatoid arthritis, diabetes mellitus type 1 and 2, and gestational diabetes.…”
Section: Rasmussen and Irgens Pregnancy-induced Hypertension In Womensupporting
confidence: 71%
“…In addition, although obesity has become more prevalent in Norway, the pregnancy population is still relatively lean. 22 Our database holds data on maternal smoking, which seems to be negatively associated with PIH, 23 although a risk factor for fetal growth restriction. As expected, adjustment for smoking increased rather than decreased the association of SGA with later PIH (data not shown).…”
Section: Strengths and Weaknesses: Possible Sources Of Confoundingmentioning
confidence: 99%
“…For Hb, the mechanisms that contribute to hypertensive disorders of pregnancy may be related with blood viscosity, which can be induced by elevation of hematocrit and Hb levels, since it has been suggested that increased blood viscosity may worsen cardiovascular function partly through an effect on blood pressure [31]. Given this finding regarding blood viscosity, it might probably explain the previous studies [7-9] that the positive associations between increased Hb and PIH were in agreement with elevated blood viscosity during pregnancy. Furthermore, free Hb is a scavenger of nitric oxide (NO), which can relax the muscle cells, increased free Hb levels may thus bind to NO and contribute to vasoconstriction and hypertension [32,33].…”
Section: Discussionmentioning
confidence: 97%
“…A recent system review including 13 trials, however, indicates that dietary intervention appears effective to reduce total and weekly gestational weight gain, but no significant effect on preventing preeclampsia and gestational diabetes [21]. For Hb, several observational studies found significantly increased Hb concentrations in women who developed PIH in the second or third trimester [7-9]. Also, a recent study showed that Hb level was positively associated with both SBP and DBP in a large cohort of healthy individuals [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation